Crush : a novel - Calhoun, Ada (Viking, an imprint of Penguin Random House LLC, 2025)
"When a husband asks his wife to consider what might be missing from their marriage, what follows surprises them both--sex, heartbreak and heart rekindling, and a rediscovered sense of all that is possible. She's happy and settled and productive and content in her full life--a child, a career, an admirable marriage, deep friendships, happy parents, and a spouse she still loves. But when her husband urges her to address what the narrow labels of husband and wife force them to edit out of their lives, the very best kind of hell breaks loose. Using the author's personal experiences as a jumping off point, Crush is about the danger and liberation of chasing desire, about the havoc it can wreak, and most of all the clear sense of self one finds when the storm passes. Destined to become a classic novel of marriage, and tackling the big questions being asked about partnership in post-pandemic relationships, Crush is a sharp, funny, seductive, and revelatory novel about holding on to everything it's possible to love--friends, children, parents, passion, lovers, husbands, all of the world's good books, and most of all your own deep sense of purpose"--